Therapeutic Plasma Exchange: Current and Emerging Applications to Mitigate Cellular Signaling in Disease - R. M. Imtiaz Karim Rony; Alireza Shokrani; Naseeb Kaur Malhi; Deborah Hussey; Rachael Mooney; Zhen Bouman Chen; Tristan Scott; Haiyong Han; Jaeger Moore; Jiahui Liu; Wendong Huang; Adolfo Garcia-Ocaña; et al. (Biomolecules)
Therapeutic plasma exchange (TPE) is a blood purification technique which functions to remove pathological plasma constituents such as autoantibodies, inflammatory cytokines, immune complexes, and extracellular vesicles (EVs) that contribute to a range of disease states. In this review, we examine current and emerging indications for TPE across cardiovascular, metabolic, neurological, inflammatory, and oncological diseases. We cover emerging preclinical animal models and new applications, emphasizing the roles of cellular signaling and EV biology in mediating plasma functions, and discuss unique therapeutic “windows of opportunity” offered by TPE. We conclude that TPE is underutilized in both preventative and precision medicine, and that next generation TPE therapies will involve personalized plasma biomarker and modulation feedback, with synergistic plasma infusion therapies to mitigate age associated disease and promote tissue rejuvenation.